Fiber-integrated phase-change reconfigurable optical attenuator - Martins, Tiago (2020)
We report on the experimental demonstration of an optical-fiber-integrated, nonvolatile transmission switching device. The operating mechanism exploits a cavity resonance spectral shift associated with an induced change in the refractive index of a high-index thin film on the polished side facet of the fiber. In the present case, a thermally induced amorphous-crystalline structural transition in a 500 nm layer of germanium antimony telluride at a distance of 500 nm from the core-cladding interface of an SMF-28 single-mode fiber delivers resonant transmission contrast >0.5 dB/mm at 1315 nm. Contrast is a function of active layer proximity to the core, while operating wavelength is determined by layer thickness—varying thickness by a few tens of nanometers can provide for tuning over the entire near-infrared telecoms spectral range.